A Critique and Review on the Book The Choice of Technology from the Monotheistic Perspective - Mohamad Amin Shafikhani; Mostafa Taqavi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The nature of modern western technology and the relation between non-western societies and this new foreign phenomenon are two important matters which alongside the increase of the intercourse of these societies and this phenomenon, have preoccupied many of their indigenous intellectuals. The book The Choice of Technology from the Monotheistic Perspective is the outcome of the reflection of one of these intellectuals that lives in a non-western country. In this book, Asghar Taherzadeh as an Iranian Muslim intellectual explained his opinions about the nature of modern western technology and the proper relation between the Iranian Shiite society and western technology based on Islamic teachings. He has made extensive use of these teachings, especially “Quran” to express his views. The purpose of this article is to introduce and critique Taherzadeh's book. For this purpose, we will compare his views in this book with some of the views expressed in the literature of Philosophy of Technology; we will also express some of his special theses.